A NEW TYPE OF ECONOMIC ANALYSIS: BUSINESS ANALYSIS - E. B. Gerasimova (Финансы: теория и практика)
A new type of economic analysis - business analysis - should be considered in its broadest sense as further development of integrated economic analysis connected with the study of business processes, business units and business models of commercial organizations. It includes investigation in such areas as marketing activities of the organization, efficient use of technological capacities, the efficiency of solutions pertaining to capital investments, financing, as well as the study of social, economic and political issues that ensure the effective and sustainable functioning of the organization. Business analysis is based on a number of methodological approaches to the study of organization activities: analysis of the dynamics in organization development; performance analysis (as performance is a main condition of sustainable development); study of organization activities in the context of organizational environment; and, finally, applying stakeholders approach, i.e. analyzing the organization performance against the requirements of stakeholders in order to ensure the creation of value for business stakeholders. Finally, the business analysis suggests proposals for solving the identified problem (or a set of problems). The article considers the procedure of business analysis as a modern method for the analysis and quality control of the organization. This new type of analysis includes investigation and control of business-processes, paperwork, and performance self-evaluation system.